Group Behavior in Organizational Culture and Inclusive Leadership in Multicultural Islamic Educational Institutions (International Journal of Education and Literature, 2025)
This study is grounded in the importance of understanding the dynamics of group behavior within multicultural Islamic education institutions , where spiritual values , organizational culture , and leadership interact to create a harmonious working climate . A strong organizational culture and inclusive leadership are believed to be the foundation for fostering collaboration , fairness , and mutual respect among members . The purpose of this study is to analyze how organizational culture and inclusive leadership styles shape group behavior within socially and culturally diverse Islamic education contexts . This research employs a qualitative method with a Systematic Literature Review (SLR) approach , reviewing relevant academic literature focused on group dynamics , work culture , and Islamic values . The findings indicate that an Islamic value - based organizational culture and inclusive leadership play a significant role in strengthening social cohesion , enhancing participation , and fostering group behavior that is both collaborative and spiritually meaningful .